2010
DOI: 10.1002/eji.201040989
|View full text |Cite
|
Sign up to set email alerts
|

Serum and organ‐associated anti‐hemoglobin humoral autoreactivity: Association with anti‐Sm responses and inflammation

Abstract: The release of hemoglobin (Hb) occurs in some infectious and autoimmune diseases characterized by inflammation. As levels of haptoglobin (Hp) fall, free Hb can cause pathology. Humoral autoreactivity to human Hb was demonstrated in the sera of systemic lupus erythematosus (SLE), leishmania and malaria patients. Serum anti-murine Hb antibody levels in lupus-prone mice also exhibited an age-dependent increase, with progressive organ sequestration; significant isotypic correlation was observed with antidsDNA anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 47 publications
2
17
0
Order By: Relevance
“…Although the SLE patients constituted a distinct cross-sectional cohort, the incidence of anti-hHb reactivity was in general agreement with previous data from our lab (17); while anti-Hb antibody levels were also significantly elevated in sera of malaria patients, antibodies in sera from rheumatoid arthritis patients and vitiligo patients did not exhibit such reactivity (Figure 1A). IgG immunoglobulins were purified from the sera of eight SLE patients (demonstrating heightened anti-hHb reactivity) and eight control subjects by Protein G affinity chromatography; IgG purified from the sera of SLE patients demonstrated significantly higher reactivity toward hHb than did IgG purified from control sera (Figure 1B).…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Although the SLE patients constituted a distinct cross-sectional cohort, the incidence of anti-hHb reactivity was in general agreement with previous data from our lab (17); while anti-Hb antibody levels were also significantly elevated in sera of malaria patients, antibodies in sera from rheumatoid arthritis patients and vitiligo patients did not exhibit such reactivity (Figure 1A). IgG immunoglobulins were purified from the sera of eight SLE patients (demonstrating heightened anti-hHb reactivity) and eight control subjects by Protein G affinity chromatography; IgG purified from the sera of SLE patients demonstrated significantly higher reactivity toward hHb than did IgG purified from control sera (Figure 1B).…”
Section: Resultssupporting
confidence: 91%
“…In this study, sera derived from a certain percentage of lupus patients exhibited anti-hHb humoral autoreactivity, in consonance with a previous report from our lab (17); IgG immunoglobulins purified from such sera also bound hHb. No obvious correlation was observed between autoimmune hemolytic anemia and the presence of anti-Hb antibodies.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In accordance, it has been recently found that autoantibodies and sera from patients suffering from diverse autoimmune conditions, but not from malaria, inhibit the in vitro growth of P. falciparum in human RBCs (Bhatnagar et al, 2011; Brahimi et al, 2011). Especially that type of autoimmunity is apparently required for protection against blood-stage malaria (Daniel-Ribeiro, 2000), that is presumably directed against autoantigens and parasite-induced neo-autoantigens on the surface of Plasmodium -infected RBCs (Wunderlich et al, 1988b,c; Fontaine et al, 2012).…”
Section: Liver Effectors Toward Blood-stage Malariamentioning
confidence: 63%